Dynamic Motion and Communication in the Streptococcal C1 Phage Lysin, PlyC - Riley, Blake T. (PLoS One, 2015)
The growing problem of antibiotic resistance underlies the critical need to develop new treatments to prevent and control resistant bacterial infection. Exogenous application of bacteriophage lysins results in rapid and specific destruction of Gram-positive bacteria and therefore lysins represent novel antibacterial agents. The PlyC phage lysin is the most potent lysin characterized to date and can rapidly lyse Group A, C and E streptococci. Previously, we have determined the X-ray crystal structure of PlyC, revealing a complicated and unique arrangement of nine proteins. The scaffold features a multimeric cell-wall docking assembly bound to two catalytic domains that communicate and work synergistically. However, the crystal structure appeared to be auto-inhibited and raised important questions as to the mechanism underlying its extreme potency. Here we use small angle X-ray scattering (SAXS) and reveal that the conformational ensemble of PlyC in solution is different to that in the crystal structure. We also investigated the flexibility of the enzyme using both normal mode (NM) analysis and molecular dynamics (MD) simulations. Consistent with our SAXS data, MD simulations show rotational dynamics of both catalytic domains, and implicate inter-domain communication in achieving a substrate-ready conformation required for enzyme function. Our studies therefore provide insights into how the domains in the PlyC holoenzyme may act together to achieve its extraordinary potency.